La mythologie selon Lévi-Strauss et Dumézil - Crépeau, Pierre (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1983)
AbstractThe works of Claude Lévi-Strauss and Georges Dumézil, undoubtedly amongst the most original of our time, can be placed in the context of a well-rounded scientific method, the work of which may only be considered complété after rigorous methodological analysis has uncovered the meaning hidden beneath the manifest meaning of word and gesture.The following pages try to make nothing more than a straightforward statement : to bring out, from immediate textual readings, the fundamental hypotheses and principal characteristics of the analytic method of these two distinct but complementary mythological undertakings.